Satisfaction of People toward the Services of Bangkhen Branch Waterworks Office, Metropolitan Waterworks Authority - คีรีรัตน์ วัลย์ลิกา; ชาญศิลป์ วัชรินทร์ (Thai Interdisciplinary and Sustainability Review, 2019)
The objectives of research were 1) to determine the level of satisfaction of people towards the services of Bangkhen Branch Waterworks Office, Metropolitan Waterworks Authority, 2) to compare satisfaction of people towards the services of Bangkhen Branch Waterworks Office, Metropolitan Waterworks Authority, based on personal factors. The research samples consisted of 329 people who received services of Bangkhen Branch Waterworks Office, Metropolitan Waterworks Authority. The data collection instrument was a questionnaire. The collected data were analyzed by Frequency, Percentage, Mean, Standard Deviation, t-test, One-Way Analysis of Variance and Least Square Method. The results showed that people moderately satisfied towards the services of Bangkhen Branch Waterworks Office, Metropolitan Waterworks Authority on the overall view. The samples who had different gender, marital status, level of educational were not different in the level of satisfaction. Samples who had different age, level of education, type of residence and income level were different in the level of satisfaction with statistical significance at the .05.